Impact of Failure to Postpone Debt Payment Obligations Suspension on Separate Creditors - Yuhelson, Yuhelson (Jurnal Cita Hukum, 2024)
Separate creditors have special rights, and rejection of a peace plan can limit these rights in terms of receiving payment from the debtor, as separated creditors will only accept payment with the lowest value between the collateral value and the actual value of the loan. This study examines the legal protection for separated creditors in the context of rejecting a peace plan in the Debt Payment Obligation Suspension (PKPU) process. The main focus of the study is to analyse the legal implications of the rejection of peace by separated creditors and how it affects their rights in the PKPU process. The methodology used is normative juridical with a statutory regulatory approach, while the legal sources used in analysing this study were obtained through library materials or secondary data. This research is also called library legal research. It can be concluded that separatist creditors are still given compensation of the lowest value among the collateral or actual value of the loan. It is directly guaranteed by collateral rights on the property owned by the creditor. The results show that the Debt Payment Obligation Suspension (PKPU) Law has yet to fully provide adequate legal protection for separatist creditors who reject the peace plan.